2017
DOI: 10.1038/srep43202
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical and morphological features of zirconia substituted hydroxyapatite nano crystals

Abstract: Zirconia doped Hydroxyapatite (HAP) nanocrystals [Ca10(PO4)6−x(ZrO2)x(OH)2]; (0 ≤ x ≤ 1 step 0.2) were synthesized using simple low cost facile method. The crystalline phases were examined by X-ray diffraction (XRD). The crystallinity percentage decreased with increasing zirconia content for the as-synthesized samples. The existence of zirconia as secondary phase on the grain boundaries; as observed from scanning electron micrographs (FESEM); resulted in negative values of microstrain. The crystallite size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(38 citation statements)
references
References 78 publications
(117 reference statements)
3
35
0
Order By: Relevance
“…The reduction in theoretical density calculated by x-ray diffraction means that the arrangement of atoms in the unit cell tends to be loose and irregular, and the interaction between the atoms is weakened, the reduction in density indicates less stability. This is consistent with the result that the x-ray diffraction peaks broadened and shifted [14][15][16][17]. Quantitative experiments were further conducted for structural analysis.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The reduction in theoretical density calculated by x-ray diffraction means that the arrangement of atoms in the unit cell tends to be loose and irregular, and the interaction between the atoms is weakened, the reduction in density indicates less stability. This is consistent with the result that the x-ray diffraction peaks broadened and shifted [14][15][16][17]. Quantitative experiments were further conducted for structural analysis.…”
Section: Resultssupporting
confidence: 86%
“…-CO 3 2 -containing BCP and pure BCP from fish bone To measure the phase composition and crystal structure of the inorganic components in the prepared materials, slow-scan fullname (XRD) (D8 ADVANCE, Germany) was used to determine the exact peak positions, and the working conditions were as follows: Cu-Kα as the radiation source and scanning at a step of 0.03°and a rate of 4°/min in the angular range of 10-60°. Using SGI workstation Ccrius2 (version 4.2) software package of American MSI Corporation and DWBS941l software to refine the powder XRD analysis data of the two samples by Rietveld refinement, the unit cell parameters of the two groups of samples were obtained and the unit cell structure integrity was compared, both samples have a two-phase structure, the theoretical density was determined using the formula = Dx ZM NV (where M is the molecular weight of the sample, N is Avogadro's number, Z is the number of molecules per unit cell and V is the unit cell volume) calculate the density of each single phase of each sample, and then calculate the calculated density of the two samples according to the formula = + Dx AD BD x x 1 2 (where A, B are the relative contribution ratios of the existing crystalline phases) [14][15][16][17]. The molecular functional groups of the sample, especially the -CO 3 2 vibration, were analyzed by fullname (FTIR) spectroscopy (1750, Perkin-Elmer, USA).…”
Section: The Characterization Ofmentioning
confidence: 99%
“…This can be due to the high amount of zirconia. Other works [ 60 , 61 ] in literature reported the reduction of the HAp crystallinity extent, due to the incorporation of silica or zirconia in the HAp lattice. Therefore, not many differences are evident by comparing this spectrum to the spectra of the 120 °C heated samples ( Figure 1 c), except for the position and intensity of the doublet in the region 1500–1300 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the formation of β-TCP, as a degradation product of the thermal degradation of the HAp phases, probably occurs also in those composites samples. In the literature, indeed, it is reported that zirconia can act as a catalyst of the decomposition reaction [ 61 ], which, thus, can also occur at a lower temperature [ 13 ]. However, β-TCP is undetectable in the spectra of the composites, because in those materials a lower HAp content is present which, thus, leads to the formation of a lower β-TCP amount.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the characteristic peaks of HA in the amorphous ZrO 2 were extremely wide, which indicated a strong chemical interaction between the enamel and confirmed that the amorphous ZrO 2 coating was amorphous. In addition, the characteristic signal of PO 4 3− of E‐Amorphous ZrO 2 had a redshift in the FTIR spectra compared with E‐Acid etched (Figure S10, Supporting Information), which indicated that the coordination between Zr 4+ and PO 4 3− to improve the connection between the coated ceramic layer and the substrate enamel (schematic illustration in Figure a).…”
mentioning
confidence: 99%